Singapore 2010 Youth Olympic Games and national pride: An examination of differences between spectators and non-spectators. Issue 1 (9th March 2015) - Leng, H. K.; Kuo, T. Y.; Baysa-Pee, Grain; Tay, Josephine
Abstract : Purpose: – Singapore hosted the inaugural Youth Olympic Games (YOG) in 2010. Prior studies have shown that a country hosting a major sports event can raise the level of national pride among its citizens. The purpose of this paper is to examine the change in national pride among spectators and non-spectators following the hosting of the YOG. Design/methodology/approach: – A longitudinal research design was employed in this study. Surveys using the General National Pride Scale to measure the level of national pride were conducted two months before and after the YOG. Findings: – Using paired t -tests, the results showed that there was a significant increase in the level of national pride among non-spectators. Research limitations/implications: – The research concurs with earlier research that hosting a major sports event can increase the level of national pride in the population. Practical implications: – From an application standpoint, this research suggests that in planning major sports events, the government should recognise that such events can increase the level of national pride even among those who have expressed no interest in the sports events. Social implications: – National pride can be fostered through the hosting of major sports events. Originality/value: – This study demonstrates that in hosting a major sports event, there is an increase in national pride even among non-spectators and those who have no interest in the event.